TiO2 nanotubes induce early mitochondrial fission in BMMSCs and promote osseointegration. (1st March 2023) - Jia, Xuelian; Wang, Le; Chen, Yicheng; Ning, Xiaona; Zhang, Zhouyang; Xin, He; Lv, Qian-xin; Hou, Yan; Liu, Fuwei; Kong, Liang
Abstract: Nanotopography can promote osseointegration, but how bone marrow mesenchymal stem cells (BMMSCs) respond to this physical stimulus is unclear. Here, we found that early exposure of BMMSCs to nanotopography (6 h) caused mitochondrial fission rather than fusion, which was necessary for osseointegration. We analyzed the changes in mitochondrial morphology and function of BMMSCs located on the surfaces of NT100 (100 nm nanotubes) and ST (smooth) by super-resolution microscopy and other techniques. Then, we found that both ST and NT100 caused a significant increase in mitochondrial fission early on, but NT100 caused mitochondrial fission much earlier than those on ST. In addition, the mitochondrial functional statuses were good at the 6 h time point, this is at odds with the conventional wisdom that fusion is good. This fission phenomenon adequately protected mitochondrial membrane potential (MMP) and respiration and reduced reactive oxygen species. Interestingly, the MMP and oxygen consumption rate of BMMSCs were reduced when mitochondrial fission was inhibited by Mdivi-1(Inhibition of dynamin-related protein 1 fission) in the early stage. In addition, the effect on osseointegration was significantly worse, and this effect did not improve with time. Taken together, the findings indicate that early mitochondrial fission plays an important role in nanotopography-mediated promotion of osseointegration, which is of great significance to the surface structure design of biomaterials.